Amyloid Proteins Methods and Protocols - Sigurdsson, Einar M.; Calero, Miguel; Gasset, María; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Amyloid diseases are characterized by the deposition of insoluble fibrous amyloid proteins. The word “amyloid” indicates a starch-like compound, and though a misnomer, continues to be the accepted term for this group of protein conformational disorders. The second edition  of Amyloid Proteins expands upon the previous edition with current, detailed protocols for the preparation of amyloid and its precursors, specific analytical methods for studying these proteins, cell culture models and assays for production of amyloid proteins, and protocols for amyloid extraction from tissue, its detection in vitro and in vivo, as well as nontransgenic methods for developing amyloid mouse models. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Amyloid Proteins, Second Edition seeks to aid scientists in the amyloid field to establish new techniques in their laboratories. Authoritative and practical, Amyloid Proteins, Second Edition seeks to aid scientists in the amyloid field to establish new techniques in their laboratories.
Keywords: Proteins .; Protein Science